Maternal asthma in Australian indigenous women and perinatal outcomes: A whole population–linked study. Issue 2 (8th August 2022) - Brew, Bronwyn K.; Gibberd, Alison; Marks, Guy B.; Murphy, Vanessa E.; Jorm, Louisa; Chambers, Georgina M.; Hartz, Donna; Eades, Sandra; McNamara, Bridgette
Abstract: Objective: To assess the association between maternal asthma and adverse perinatal outcomes in an Australian Indigenous population. Methods: This prospective cohort study included all Indigenous mother and baby dyads for births from 2001 to 2013 in Western Australia ( n  = 25 484). Data were linked from Western Australia Births, Deaths, Midwives, Hospital, and Emergency Department collections. Maternal asthma was defined as a self‐reported diagnosis at an antenatal visit or hospitalization or emergency visit for asthma during pregnancy or less than 3 years before pregnancy. Associations with birth, labor, and pregnancy outcomes were assessed using generalized estimating equations. Asthma exacerbation during pregnancy and stratification by remoteness was also assessed. Results: Maternal asthma was associated with placental abruption (adjusted odds ratio [aOR], 1.59 [95% confidence interval (CI), 1.07–2.35]), threatened preterm labor (aOR, 1.58 [95% CI, 1.39–1.79]), and emergency cesarean sections (aOR, 1.27 [95% CI, 1.13–1.44]). These risks increased further with an asthma exacerbation during pregnancy or if the mother was from a remote area. No associations were found for low birth weight, preterm birth, small for gestational age, or perinatal mortality. Conclusion: Maternal asthma in Indigenous women is associated with an increased risk of emergency cesarean sections, placental abruption, and threatened preterm labor. These risks may be mitigated by improved management of asthma exacerbations during pregnancy. Synopsis: Maternal asthma in Australian Indigenous women is associated with an increased risk in emergency cesarean sections, placental abruption, and threatened preterm labor.